Pengalaman Ibu dalam Pemberian ASI Eksklusif pada Anak dengan Kondisi Stunting - Nani Nurhaeni; Dessie Wanda; Risna Merysa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
One of the factors associated with the incidence of stunting is exclusive breastfeeding. This literature study aims to explore the experience of mothers in exclusive breastfeeding for children with stunting conditions. The authors have systematically analyzed studies published between 2015 and 2021 through identification in Scopus, Wiley Online Library, and ProQuest. The keywords used in the article search were mother AND breastfeeding AND “experience OR practice” AND “stunting OR malnutrition”. A total of 10 articles have been analyzed and several themes have been obtained, namely: 1) the relationship between exclusive breastfeeding and the incidence of stunting, 2) factors that influence exclusive breastfeeding, and 3) the benefits of breastfeeding. The practice of exclusive breastfeeding in children is one of the factors that can reduce the incidence of stunting. Thus, it is necessary to involve all parties to increase the success rate of exclusive breastfeeding in accordance with WHO recommendations.Keywords: exclusive breastfeeding; experience; stunting ABSTRAK Salah satu faktor yang berhubungan dengan kejadian stunting yaitu pemberian ASI eksklusif. Studi literatur ini bertujuan untuk mengeksplorasi pengalaman ibu dalam pemberian ASI eksklusif pada anak dengan kondisi stunting. Penulis telah menganalisis secara sistematis studi yang diterbitkan antara 2015 dan 2021 melalui identifikasi di Scopus, Wiley Online Library, dan ProQuest. Kata kunci yang digunakan dalam melakukan pencarian artikel yaitu mother AND breastfeeding AND “experience OR practice” AND “stunting OR malnutrition”. Sebanyak 10 artikel telah dianalisis dan diperoleh beberapa tema yaitu: 1) hubungan pemberian ASI eksklusif dengan kejadian stunting, 2) faktor yang memengaruhi pemberian ASI eksklusif, serta 3) manfaat ASI. Praktik pemberian ASI eksklusif pada anak merupakan salah satu faktor yang dapat mengurangi tingkat kejadian stunting. Dengan demikian diperlukan keterlibatan dari semua pihak untuk meningkatkan angka keberhasilan pemberian ASI eksklusif sesuai dengan rekomendasi WHO.Kata kunci: ASI eksklusif; pengalaman; stunting